The role of genital mycoplasma infection in female infertility: A systematic review and meta-analysis - Tantengco, Ourlad Alzeus G.; de Castro Silva, Mariana [UNESP]; Velayo, Clarissa L. (Wiley, 2021)
Problem: Recent studies show that lower genital tract infection with genital mycoplasma may be associated with the pathology of female infertility. However, this association remains controversial due to the variable prevalence, sample sizes, and different methods used to diagnose genital mycoplasma infection. The aim of the present meta-analysis was to gain better understanding of the specific impact of genital mycoplasma on female infertility. Method of Study: A systematic review of literature on the association of genital mycoplasma (Mycoplasma genitalium, Mycoplasma hominis, Ureaplasma parvum, and Ureaplasma urealyticum) infection and female infertility was performed using three electronic databases: PubMed, Scopus, and CINAHL, from January 2000 to January 2020. Pooled odds ratio (OR) and 95% confidence intervals for genital mycoplasma infection and female infertility were derived from a fixed effects model. Results: This meta-analysis included eight studies conducted in six countries. Based on the results, women with infertility had a statistically higher odds of having any genital mycoplasma infection (p <.0001) compared to the control group. The pooled OR of all the included studies was 3.82 (95% CI: 2.55, 5.72). There was an unremarkable heterogeneity in all the studies included in this meta-analysis (I2 = 0%, p =.48). A subgroup analysis also showed that M. genitalium, M. hominis, and U. urealyticum infections are significantly associated with female infertility. Conclusion: Our meta-analysis showed a significant association between M. genitalium, M. hominis, and U. urealyticum infections and female infertility. This evidence supports the development of guidelines for the diagnosis and treatment of genital mycoplasma infections to prevent female infertility.
Keywords: human reproduction; infection; inflammation; mollicutes; sexually transmitted disease